Polyethylene glycol/modified carbon foam composites for efficient light-thermal conversion and storage. (16th July 2021) - Lin, Fankai; Zhang, Xiaoguang; Liu, Xianjie; Xu, Yunfei; Sun, Zhenhua; Zhang, Liangpei; Huang, Zhaohui; Mi, Ruiyu; Min, Xin
Abstract: The limited light absorption, low thermal conductivity, and poor shape stability restrict the widespread application of organic phase change materials (PCMs). Herein, carbon foam (CF) with the light, inter-connective porous, and high-strength was developed based on the phenolic resin to encapsulate organic PCMs, and multi-walled carbon nanotubes (MWCNTs) were added to improve the compressive strength and light absorption at the same time. Then, the polyethylene glycol (PEG) was encapsulated in the CF/MWCNTs composite via a vacuum impregnation method. The modified CF composite could act as an efficient heat transfer channel to improve the thermal conductivity and light-thermal conversion efficiency of PEG. As a result, the PEG/CF composites displayed a high latent enthalpy (156.3 J/g to 170.9 J/g) and an excellent light-thermal conversion efficiency (61%–74%). Furthermore, the PEG/CF10 exhibited the highest thermal conductivity of 0.68 W/(m∙K), which is about 2.24 times higher than that of pure PEG. The as-prepared PEG/CF composites with mechanical strength and thermal stability could exhibit great potential in solar energy utilization, building energy conservation, and waste heat recovery. Graphical abstract: Image 1 Highlights: A phenolic resin carbon foam modified by MWCNTs has been first designed by a simple template method. The modified carbon foam with inter-connective porous act as a good supporting material to encapsulate organic PCMs. PEG/CF composites displayed an enhanced thermal conductivity and light-thermal conversion efficiency. The light-thermal conversion and storage mechanism has been investigated.